Sociodemographic Factors and Predictors of Social Media Addiction in University Students - Martín, Francisco Mena; Urruchi, Abraham Eudes Pérez; Amador, Yanedsy Díaz; Espinoza, Marilú Elena Barreto (Journal of Posthumanism, 2026)
Introduction: Social media addiction in university students recognizes sociodemographic factors as a global public health problem, which calls into question the impact that it may have on the positive psychological and social functioning of this population. Objective: To analyze the predictive value of sociodemographic factors and usage habits in social media addiction in university students. Material and method: A quantitative, descriptive, correlational-predictive, non-experimental study. 710 students of both sexes, between 18 and 35 years old, from urban and rural areas of the Guayas province, Ecuador, participated during the period from January to June 2025. The sample was characterized socio-demographically and social media habits and use were measured. Bivariate analysis (Spearman's Rho coefficient 95%CI) and multivariate analysis (RLO) were performed with the Jamovi 2.3.28 statistical software. Results: There was a predominance of women (62.11%), urban residence (72.25%), single marital status (82.11%), low socioeconomic status (69.01%), connection time greater than 4 hours (67.89%), mostly used platform Facebook (32.12%), linked to the activities of viewing photos and videos (44.37%), with a high level of addiction to social networks (67.61%). The variables age, place of residence, socioeconomic status, connection time and need for connection were statistically significant in the inferential analysis. Conclusions: The findings of the ordinal logistic regression model predict that age and connection time contribute significantly to the explanation of addiction to social networks in university students.